Effects of The Acidity of Beverages on The Hard Tissues of Teeth - Chaqqonov Faxriddin Xusanovich (Scientific Trends, 2024)
In the Republic of Uzbekistan, an online survey was conducted among different age groups to determine which drinks are consumed most often (240 respondents). The pH value of 26 drinks was measured using a litmus test and a pH meter. The beverage was determined based on these ph values and distributed to a group of liquids according to their erosion potential. Five drinks were used for the enamel resistance test (ERT): pineapple juice, lemon juice, red wine, white wine, and green tea. The most aggressive fluid for the hard tissues of the teeth was determined. As a result of the experiment, the drink that has the most aggressive impact on the hard tissue of the tooth is lemon juice and within 3 days reduces the resistance of the enamel against caries by 3.33 times.
Keywords: Beverage, hard tooth tissue, acidity of caries resistance